Partial characterization of a filamentous virus associated with ringspot disease of citrus - Y.S.AHLAWAT, R.P. PANT and (Indian Phytopathology, 2002)
Ringspot disease is one of the major constraints in citrus production in India and widely distributed in citrus plantations in Punjab, Haryana, Rajasthan, Uttar Pradesh, Andhra Pradesh and Karnataka with an incidence ranging from 10-100%. Commercial cultivars of Citrus sinensis, C. reticulata and C. aurantifolia including kinnow mandarin (hybrid of king and willow mandarin) are susceptible to ringspot infection. The disease is transmitted by wedge grafting and dodder (Cuscuta reflexa) but not through seed, soil, aphid and nematode species. However, the virus [?citrus ringspot virus] was detected in pollens, collected from ringspot infected citrus trees, in IEM tests using virus specific antiserum, suggesting the possibility of pollen transmission of this virus. Two types of virions measuring 640 nmX15 nm and 300-600 nmX6-10 nm are known to be associated with ringspot disease. The first component has already been identified as a member of the capillovirus group while the results indicated that the latter was related to members of ’Ophioviruses’. The coat protein of the virus contains 2 major polypeptides of 60 and 67 KDa. Polyclonal antibodies of the virus were prepared and used for detection of this virus in ELISA and IEM tests.